Clinical and immunological studies in twenty families with ataxia-telangiectasia - Ersoy, Fügen; Berkel, A. İzzet (The Turkish Journal of Pediatrics, 1974)
Thirty-one patients with A-T from 20 families, were subjected to clinical evaluation. Various tests for cellular and humoral immunity were carried out on these patients, their four healthy siblings and on 23 of the parents. Twenty-two healthy children of the same age were also subjected to similar tests. The consanguinity rate among the parents was 85 %. The absolute lymphocyte count was low in 54.5 %, and delayed hypersensitivity responses to five different skin test antigens were impaired in 65 % of the patients. In vitro response of the lymphocytes to PHA, Candida and SKSD antigens were low in these patients with respective values of 50 %, 65 % and 80 %. Mixed lymphocyte culture response was good in 11 out of 15 patients studied. T cell rosettes were significantly low. Serum IgA deficiency was present in 42 % of the patients and serum IgE was low in 7 out the 9 patients investigated. Salivary IgA was low in 4 out of 15 examined patients. The red cell ADA’se levels were normal in 9 patients studied. No correlations between a consistent pattern of tests and/or the severity of infection in these patients was observed.